2013
DOI: 10.1016/j.tcb.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Use the force: membrane tension as an organizer of cell shape and motility

Abstract: Many cell phenomena that involve shape changes are affected by the intrinsic deformability of the plasma membrane. Far from being a passive participant, the plasma membrane is now known to physically, as well as biochemically, influence cell processes ranging from vesicle trafficking to actin assembly. Here we review current understanding of how changes in plasma membrane tension regulate cell shape and movement as well as how cells sense plasma membrane tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
473
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(501 citation statements)
references
References 80 publications
12
473
0
1
Order By: Relevance
“…It has been shown that increasing membrane tension results in numerous intracellular signaling events, including the inhibition of Rac activation and actin assembly (20,39). Our results agree with these findings.…”
Section: Membrane Tension As a Signal For Late-stage Phagocytosissupporting
confidence: 92%
See 1 more Smart Citation
“…It has been shown that increasing membrane tension results in numerous intracellular signaling events, including the inhibition of Rac activation and actin assembly (20,39). Our results agree with these findings.…”
Section: Membrane Tension As a Signal For Late-stage Phagocytosissupporting
confidence: 92%
“…On a purely physical level, tension acts to restrict protrusions, forcing the cell to remain rounded. However, there is evidence that membrane tension is also involved in signaling intracellular processes via membrane-associated sensors (39). Moreover, membrane tension has been shown to play a role in phagocytosis-related signaling (20,21).…”
Section: Estimation Of Tension At the Onset Of Late-stage Contractionmentioning
confidence: 99%
“…However, an emerging field of research on ion channel regulation in recent years has been to explore the impact of membrane biophysical properties on the activity of different ion channels (16,17). It has been shown that membrane biophysical properties such as static plasma membrane tension (SPMT) have a significant impact on functions of some ion channels ranging from directly gating (e.g.…”
mentioning
confidence: 99%
“…In general, the mechanical phenotype of cells is related to their own vital parameters. 2,3,[6][7][8][9][10][11][12][13] The Atomic Force Microscope 14,15 (AFM) has proved to be a valuable tool for the quantitative characterization of static and frequency-dependent mechanical properties of micro-and nanostructures, including biological specimens, [16][17][18][19][20][21][22] thanks to its ability to sense and apply nanoscale forces, and to capture the three-dimensional topography of samples in different environments, including physiological buffers. Several papers report on the measurement by AFM of modulations in cellular elasticity induced by variations in the environmental conditions, like drugs targeting specific cytoskeletal components, [23][24][25] by changes in the elasticity and surface energy of the substrate, [26][27][28] as well as by the correlation between cells' elasticity and their patho-physiological state, including cancer diseases.…”
Section: Introductionmentioning
confidence: 99%